Infrastructural Development Problems at Thoseghar: A Tourist Destination in Satara District, Maharashtra - Chavan, Rajashri Ramesh; Bhola, Sarang Shankar (Indian Journal of Marketing, 2013)
The present paper probes into the problems and prospects of infrastructural development at Thoseghar, an exotic waterfall in Satara district. Tourists visit Thoseghar in hoards during the rainy season. The destination has much potential to develop as a major tourist destination that can attract a large number of tourists. It is observed that tourists from not only Satara, but from adjacent districts and metros like Mumbai and Pune visit the place during weekends and holidays. A structured schedule was used to identify problems with infrastructural facilities that contains 35 variables stating different aspects viz. Road connectivity, Civic administration, Transport and Traffic management, Tourist facilities, Maintenance and management of tourist attraction and other services. Likert scale has been used to infer the opinion of the sample respondents on the importance level of facilities, and its satisfaction level with respect to destination Thoseghar. Researchers observed that Thoseghar is a memorable one-day trip covering the Thoseghar Waterfalls, Chalkewadi Windmill Farms, offers panaromic views of forts, valleys, and clouds, and the Urmodi Dam further enriches the one-day trip. There are more gaps in importance and its satisfaction level towards facilities like Traffic management, Public utility, Guide availability, Parking facility, Mobile services and Hygiene of wayside amenities, restaurants and Dhabas. These gaps are prominent requirements of tourist destinations to attract a large number of tourists. The research concludes that the authorities need to focus on Communication services (like telephone and mobile connectivity) , Parking facility, Traffic management and General upkeep of hotels at Thoseghar.